Screening a Strain of Aspergillus niger and Optimization of Fermentation Conditions for Degradation of Aflatoxin B1 - Wei Zhang; Beibei Xue; Mengmeng Li; Yang Mu; Zhihui Chen; Jianping Li; Anshan Shan (Toxins, 2014)
Aflatoxin B1, a type of highly toxic mycotoxin produced by some species belonging to the Aspergillus genus, such as Aspergillus flavus and Aspergillus parasiticus, is widely distributed in feed matrices. Here, coumarin was used as the sole carbon source to screen microorganism strains that were isolated from types of feed ingredients. Only one isolate (ND-1) was able to degrade aflatoxin B1 after screening. ND-1 isolate, identified as a strain of Aspergillus niger using phylogenetic analysis on the basis of 18S rDNA, could remove 26.3% of aflatoxin B1 after 48 h of fermentation in nutrient broth (NB). Optimization of fermentation conditions for aflatoxin B1 degradation by selected Aspergillus niger was also performed. These results showed that 58.2% of aflatoxin B1 was degraded after 24 h of culture under the optimal fermentation conditions. The aflatoxin B1 degradation activity of Aspergillus niger supernatant was significantly stronger than cells and cell extracts. Furthermore, effects of temperature, heat treatment, pH, and metal ions on aflatoxin B1 degradation by the supernatant were examined. Results indicated that aflatoxin B1 degradation of Aspergillus niger is enzymatic and this process occurs in the extracellular environment.